(untitled) (INNOVATIVE ECONOMY, 2026)
Liuba A.I. ACCOUNTING FOR LOGISTICS OPERATIONS OF IMPORTED GOODS: ORGANIZATIONAL AND METHODOLOGICAL ASPECTS Purpose. The aim of the article is to substantiate theoretical approaches and develop practical recommendations for improving the organization and methodology of accounting for logistics operations related to the import of goods, taking into account delivery terms, regulatory and legal framework, and modern digital transformations. Methodology of research. The study applies general scientific and specific research methods, including analysis and synthesis to generalize approaches to accounting for logistics operations; comparative analysis to assess the consistency between accounting, civil, and customs regulations; a system approach to identify the interrelations between logistics and accounting processes; logical generalization to formulate conclusions. Findings. The research reveals that accounting for import operations is shaped by logistics delivery terms, regulatory frameworks, and the economic substance of transactions. An integrated approach to asset recognition is substantiated, combining risk transfer, control over assets, and documentary evidence. The impact of delivery terms on the initial cost formation of inventories, particularly through logistics-related costs, is determined. The study proposes recognizing goods in transit as a separate accounting object. Furthermore, the role of digital initiatives such as eFTI and the EU Customs Single Window in transforming accounting processes is highlighted. Originality. The approach to the recognition of imported goods as assets based on the concept of economic control has been improved; a logistics and accounting model for the formation of initial cost has been developed; the feasibility of separating goods in transit as an independent accounting object through the use advanced inventory account analytics has been substantiated, in particular through the use of subaccounts for accounting for imported goods in transit and at the customs clearance stage. Practical value. The proposed approaches can be applied by enterprises in developing accounting policies, improving inventory accounting, and implementing digital solutions. Their adoption enhances the reliability of financial reporting, optimizes logistics costs, and supports effective decision-making in foreign economic activities. Key words: import operations accounting, logistics, Incoterms 2020, initial cost of goods in transit, logistics costs, digital accounting.